Analisis Pelaporan Zakat, ICSR, Dewan Pengawas Syariah dan Leverage dalam Mengungkapkan Kinerja Bank Umum Syariah di Indonesia - Gustika Nurmalia; Yudhistira Ardana (Cakrawala: Jurnal Studi Islam, 2019)
This study aims to empirically prove the influence of zakat reporting, ICSR, sharia supervisory board and leverage on company performance at Islamic Commercial Banks with an observation period of 2016-2018. The sample in this study is 11 BUS with purposive sampling. Data analysis uses multiple linear regression analysis. The results indicate that the zakat reporting and sharia supervisory board have a significant effect on BUS performance, while ICSR and leverage have no significant effect on performance